2021
DOI: 10.1093/plcell/koab229
|View full text |Cite
|
Sign up to set email alerts
|

COPII Sec23 proteins form isoform-specific endoplasmic reticulum exit sites with differential effects on polarized growth

Abstract: COPII, a coat protein complex that forms vesicles on the endoplasmic reticulum (ER), mediates trafficking to the Golgi. While metazoans have few genes encoding each COPII component, plants have expanded these gene families, leading to the hypothesis that plant COPII has functionally diversified. In the moss Physcomitrium (Physcomitrella) patens, the Sec23/24 gene families are each composed of seven genes. Silencing Sec23/24 revealed isoform-specific contributions to polarized growth, with the closely related S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Interestingly, a recent report provided evidence that the assembly and cellular secretion of coronaviruses and other budding viruses employs a direct connection of ERGIC with endosomes, bypassing the passage from Golgi stacks ( Saraste and Prydz, 2021 ). Cargo Golgi-bypass has also been recently speculated in Physcomitrella patens , based on the observation that Sec23 isoforms form distinct and functionally specific COPII/ERes, with some of them affecting ER to Golgi trafficking and polarized growth (i.e., conventional secretion), while others proved unrelated to polarized growth, while affecting specific cargo secretion ( Chang et al, 2021 ). In fact, the multiple isoforms of COPII components present in plants ( Chung et al, 2016 ) and mammals ( Jensen and Schekman, 2011 ) may point to functional diversity, rather than redundancy, related not only to the cargoes selected but also the trafficking route followed after ER-exit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent report provided evidence that the assembly and cellular secretion of coronaviruses and other budding viruses employs a direct connection of ERGIC with endosomes, bypassing the passage from Golgi stacks ( Saraste and Prydz, 2021 ). Cargo Golgi-bypass has also been recently speculated in Physcomitrella patens , based on the observation that Sec23 isoforms form distinct and functionally specific COPII/ERes, with some of them affecting ER to Golgi trafficking and polarized growth (i.e., conventional secretion), while others proved unrelated to polarized growth, while affecting specific cargo secretion ( Chang et al, 2021 ). In fact, the multiple isoforms of COPII components present in plants ( Chung et al, 2016 ) and mammals ( Jensen and Schekman, 2011 ) may point to functional diversity, rather than redundancy, related not only to the cargoes selected but also the trafficking route followed after ER-exit.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports have shown that Sec24 isoforms (paralogs) are selective towards distinct cargoes ( Roberg et al, 1999 ; Miller et al, 2002 ) or are non-uniformly distributed to ERes in S. cerevisiae ( Iwasaki et al, 2015 ). In addition, in the moss Physcomitrella patens , COPII Sec23 isoforms have been shown to form specific ER-exit sites with differential effects on polarized growth ( Chang et al, 2021 ). A hypothesis that cargo identity may define the formation of distinct COPII complexes and vesicle populations during plant development and in response to stress has also been proposed ( Tanaka et al, 2013 ; Chung et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Multiple paralogs of COPII protein components were also discovered in plants [ 59 ]. The expression pattern, subcellular localization, and function of the COPII protein paralogs showed a significant difference [ 60 , 61 , 62 , 63 ]. SEC23A/SEC23D [ 64 ], SEC31A/B [ 61 , 65 ] and Sar1B/C [ 62 ] had been reported to be required in pollen development.…”
Section: Main Components Of the Secretory Pathwaymentioning
confidence: 99%
“…SEC23A/SEC23D [ 64 ], SEC31A/B [ 61 , 65 ] and Sar1B/C [ 62 ] had been reported to be required in pollen development. In Physcomitrium patens , Sec23D is localized in the presumptive ER-exit sites [ 60 ]. The knockout of the Sec23 d gene suppressed the protein transportation between ER and Golgi and protein secretion in the mutant plants, leading to ER morphology defects and ER stress [ 60 ].…”
Section: Main Components Of the Secretory Pathwaymentioning
confidence: 99%
See 1 more Smart Citation